Relasi dan Reposisi Agama dan Negara: Tatapan Masa Depan Keberagamaan di Indonesia - Sofyan Hadi (Millah: Journal of Religious Studies, 2011)
This paper discusses the historicity of Islam and state relations, diversity of views among Muslim traditionalists and modernists on the relation of Islam and the state, and ideal configuration of the relation of Islam and the state. By mapping analysis of contemporary-crucial cases, it is found the need to reposition of the state as a facilitator of religious life by taking part religion in all aspects of civic life.